Approaches to Assess Market Power in the Online Networking Market - Cheng, Shin-Ru (Science and Technology Law Review, 2021)
Facebook, the world’s largest online networking platform, is the subject of multiple antitrust investigations by various state and federal regulators. Yet scholars and practitioners remain divided on how to measure Facebook’s market power. Some argue that conventional approaches for identifying market power are suitable for the online networking market. This Article argues such conventional approaches are inadequate for assessing market power in online networking markets. This Article begins by introducing the traditional approaches that courts have employed to assess market power: the direct effects approach, the Lerner Index approach, and the market share approach. It next describes Facebook’s business model and shows that, because Facebook is a two-sided market, these traditional approaches should not be applied to Facebook. Instead, the Article proposes that the information gaps, switching costs, and entry barriers approaches are better suited for assessing the market power of online networking platforms. The Article thus concludes by proposing a legal framework for assessing market power in online networking platforms which employs such non-traditional approaches. While this Article uses Facebook as the main case study, this paper’s findings are equally applicable to similar online networking platforms.